Controlling Blood Sugar Levels with Diet in Diabetes Mellitus Sufferers: Literature Review - Elok Kurniasari; Wachidah Yuniartika (International Journal of Public Health, 2024)
Wrong eating patterns in Diabetes Mellitus (DM) sufferers will cause blood sugar levels increases, so dietary factors or planning eating is very important in control blood sugar levels. Good diet​​ become component main success DM management. The purpose of study This is For know control blood sugar levels with diet in diabetes mellitus sufferers through literature study. Search journal using Google database schoolar, pubmed , conchrance and springer ago produced 3 journals For followed up. Journal analyzed using appropriate PRISMA diagrams with inclusion criteria used​ that is journal use Language English and Indonesian, using design RCT research, and published between January 2018 to June 2024 about control blood sugar levels with diet in diabetes mellitus sufferers. Proven diet capable lowering blood sugar in diabetes mellitus sufferers.